Applications of nano palm oil fuel ash and nano fly ash in concrete - Hamada, Hussein M.; Jokhio, Gul Ahmed; Fadzil, Mat Yahaya; Humada, Ali Mahmood (IOP Publishing, 2018)
This paper discusses the applications of Nano waste materials including palm oil fuel ash and fly ash in the concrete production. The implementation of nanotechnology has been instrumental in the development of significant interest among the stakeholders to improve the mechanical and chemical properties of materials involved in the production of concrete. Although many researchers have shown the potential of nanomaterials to increase strength and durability of concrete and improve its physical and chemical properties, there is still a knowledge gap regarding the preparation of Nano waste materials from agricultural waste to use as cement replacement instead of non-renewable materials. Therefore, it should be focused on to study Nano- waste materials to benefit from these characteristics during preparation of concrete mixtures. Therefore, this paper highlights the potential of waste materials in the Nano size to partially replace cement in concrete and achieve the same or better result than the traditional concrete. This paper recommends to conduct further experimental works to improve the concrete material properties by investigating the properties of waste materials in Nano size.